Improved physiological markers of omega-3 status and compliance with omega-3 supplementation in Division I track and field and cross-country athletes: a randomized controlled crossover trial - Graybeal, A. J.; Helms, B.; Couris, K.; Thomas, D.; Johnston, T.; Dahan, V.; Escobedo, N.; Willis, J. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2022)
A sufficient omega-3 index may enhance cardiovascular function, enhance performance, and decrease inflammation. However, most collegiate athletes are deficient in omega-3s, requiring supplementation. A new type of omega-3 (N3) supplement, Enhanced Recovery™ (ER), claims to improve N3 index while addressing the current issues with traditional supplementation. The purpose of this study was to determine if ER improves N3 status and enhances compliance compared with the current standard in collegiate Division I Track and Field and cross-country athletes during a competitive season. Twenty-five (male = 15 and female = 10) athletes completed this longitudinal, randomized controlled crossover trial. Measurements of N3 status were collected at baseline prior to supplementation, and every 2 weeks for 6 weeks with a 33- to 36-day washout period before crossing over. Supplement compliance and dietary intake of N3 rich foods were collected throughout. Visual analog scales and an exit survey asked questions regarding each treatment. Results showed that N3 index increases within 6 weeks (p < .001) for ER (+37.5%) and control (CON; +55.1%), with small differences between treatments at Weeks 4 (ER = 7.3 ± 1.0; CON = 7.7 ± 1.1; p = .043) and 6 (ER = 7.4 ± 1.2; CON = 7.9 ± 1.2; p = .043). Dietary intake of N3-rich foods and supplement compliance were significant drivers of improvements in N3 status (p < .050). Compliance was not different between treatments but was affected by sex (males = 90.0 ± 17.0% and females = 76.5 ± 21.0%; p = .040), likability (p = .001; r = .77, p < .001), ease (p = .023; r = .53, p = .006), and supplement preference (p = .004), which appeared to favor ER. We conclude that consumption of N3-rich foods and consistent supplementation should be implemented for improvements in N3 status in collegiate athletes, but taste tests/trial periods with ER or CON may help determine preference and improve compliance.